Kommentaarid Priit Välja arvamusloo „Riik soovib rohkem arste, kuid kas kõik tudengid mahuvad Tartusse õppima?“ kohta - Talving, Peep; Starkopf, Joel; Peedu, Agris; Kingo, Külli (Eesti Arst, 2025)
Eesti Arst 2025; 104(2):75–78